Dependence of Oak-Related Volatile Compounds on the Physicochemical Characteristics of Barrel-Aged Wines - Pedro Rodríguez-Rodríguez; Encarna Gómez-Plaza (Food Technology and Biotechnology, 2012)
This paper focuses on the effect of some of the physicochemical characteristics of wines such as volatile acidity, titratable acidity, pH, free SO2 and alcohol content on the accumulation of oak-related volatile compounds in barrel-aged wines, in order to give more light on the contradictory results found by other authors in this respect. For this, three different single variety wines were aged for twelve months in barrels with the same characteristics (same cooperage, wood origin, toasting level and volume), repeating the experiment in two consecutive years. Our results show that the percentage of wine alcohol and its titratable acidity positively correlated with the final concentration of vanillin and guaiacyl compounds in the oak-matured wines and negatively with the cis- and trans-β-methyl-γ-octalactone concentration. Therefore, when studying the effect of oak barrel variables (oak origin and seasoning, size of the barrel, number of uses, etc.) on the concentration of oak-related volatile compounds in wine, the effect of the physicochemical variables of the wine, especially titratable acidity and alcohol content, should also be taken into account since the final wine aroma composition will also depend on these characteristics.